Моніторинг емерджентних властивостей розвитку промислових підприємств за умов посилення інтеграційних процесів - Гурочкіна, Вікторія Вікторівна; Менчинська, Олена Миколаївна (Вісник Хмельницького національного університету, 2020)
У статті акцентовано увагу на важливості моніторингу емерджентних властивостей розвитку промислових підприємств. Виокремлено, систематизовано і досліджено основні групи показників, що визначають емерджентні властивостей розвитку індустріальних підприємств, а саме: показники концентрації прибутковості, що характеризують можливість промислового підприємства акумулювати фінансові ресурси певний період часу; показники рівня інтеграції, які характеризують можливість підприємства бути повноцінним партнером в об‘єднанні та стійких взаємозв‘язках із партнерами та/або стейкхолдерами; показники балансу структури підприємства, які характеризують цілісність підприємства та його стабільність, що проявляється у незмінних стратегічних позиціях компанії; групу показників зміцнення потенціалу бізнес-структури, які дають можливість досліджувати посилення конкурентоспроможності, ефективне масштабування та локалізацію виробничих потужностей структурних одиниць, показують зміни у показниках капіталізації та частки ринку; показники соціальної відповідальності промислових підприємств, що аналізують збалансовану діяльність, результатом якої є поєднання у собі потрійного ефекту : економічного, соціального та екологічного, перехід до циркулярної економіки та податкової конкурентоспроможності підприємства; показники інноваційності підприємства, які характеризують досягнення новітніх результатів у випуску та під час виробництва продукції, що підвищують рівень автоматизації праці, інноваційної активності, фінансового забезпечення інноваційної діяльності підприємства.

The article focuses on the importance of monitoring emergence properties of industrial enterprises. The main groups of indicators that determine the emergence properties of industrial enterprises development are separated, systematized and investigated. Profit concentration indicators that characterize the ability of an industrial enterprise to accumulate financial resources over a period of time; indicators of the level of integration that characterize the enterprise's ability to be a fully-fledged partner in a merger and stable relationship with partners and / or stakeholders; indicators of the balance of the structure of the enterprise, characterizing the integrity of the enterprise and its stability, which is manifested in the unchanged strategic positions of the company; a group of business structure empowerment indicators that enable exploration of competitiveness enhancement, efficient scaling and localization of production units of structural units, show changes in capitalization and market share; Indicators of social responsibility of industrial enterprises analyzing balanced activities, which result in a combination of a triple effect: economic, social and environmental, the transition to a circular economy and tax competitiveness of the enterprise; indicators of enterprise innovation, which characterize the achievement of the latest results in the production and production of products, which increase the level of automation of work, innovation activity, financial support of innovative activity of the enterprise. The study concludes that the method of monitoring emergence properties of an industrial enterprise should include indicators of concentration of profitability, level of integration of connections and interaction, characteristics of balance of the structure of the enterprise and its stability, strengthened capacity, responsible behavior and enhancement of innovative activity and financial support. With the rapid positive changes of the above indicators in economic systems (both at the macro and micro levels), new qualities may emerge in systems that were not previously inherent in its individual components.
Keywords: розвиток; емерджентні властивості; промисловість; моніторинг; методика; інноваційний розвиток; інтеграційні процеси; development; emergenсe properties; industry; monitoring; methodology; innovative development; integration processes